Early and Late Endograft Limb Proximal Migration with Resulting Type 1b Endoleak following an EVAR for Ruptured AAA - Patrick T. Jasinski; Demetri Adrahtas; Spyridon Monastiriotis; Apostolos K. Tassiopoulos (Case Reports in Vascular Medicine)
Introduction. Seal zone failure after EVAR leads to type 1 endoleaks and increases the risk of delayed aortic rupture. Type 1b endoleaks, although rare, represent a true risk to the repair. Case Presentation. We report the case of a 65-year-old female who underwent emergent endovascular repair for a ruptured infrarenal abdominal aortic aneurysm and developed bilateral type 1b endoleaks following proximal migration of both endograft limbs. The right-side failure was diagnosed within 48 hours from the initial repair and the left side at the 1-year follow-up. Both sides were successfully treated with endovascular techniques. A review of the literature with an analysis of potential risk factors is also reported. Conclusion. For patients undergoing EVAR for ruptured AAA and with noncalcified iliac arteries, more aggressive oversizing of the iliac limbs is recommended to prevents distal seal zone failures.